2022
DOI: 10.1136/bmjopen-2022-060829
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and vaccine passports: a cross-sectional conjoint experiment in Japan

Abstract: ObjectivesWhile the development of vaccines against the Novel Coronavirus (COVID-19) brought hope of establishing herd immunity and ending the global pandemic, vaccine hesitancy can hinder the progress towards herd immunity. In this study, by analysing the data collected when citizens undergo public health restrictions due to the pandemic, we assess the determinants of vaccine hesitancy, reasons for hesitation and potential effectiveness of vaccine passports used to relax public health restrictions on mitigati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 51 publications
7
41
1
Order By: Relevance
“…Participants who reported the greater magnitude of behavior change in the present study were women, younger generations, those without children, and those with higher incomes. Apart from income, those demographic categories correspond to the population who reported a hesitant attitude towards the vaccines at the early stage of the Japanese vaccine program [ 17 , 21 , 22 , 23 ]. It can be interpreted that individuals who were unwilling to receive vaccines were more motivated to prevent virus transmission through behavior change.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants who reported the greater magnitude of behavior change in the present study were women, younger generations, those without children, and those with higher incomes. Apart from income, those demographic categories correspond to the population who reported a hesitant attitude towards the vaccines at the early stage of the Japanese vaccine program [ 17 , 21 , 22 , 23 ]. It can be interpreted that individuals who were unwilling to receive vaccines were more motivated to prevent virus transmission through behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those who were reluctant to change behaviors were more willing to receive vaccines. It is reported that the most common reasons for vaccine hesitancy in Japan were side effects and uncertain safety [ 23 ]. Individuals accepting these risks appeared to have prioritized maintaining pre-pandemic behaviors as much as possible, while those who were unwilling to take risks associated with the vaccines chose to prevent the illness through behavior changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations